The Use of Process Thinking in the Industrial Practice – Preliminary Survey - Eva Šírová (Tehnički Vjesnik, 2019)
Nowadays, the main implementation weakness of production management methods as Lean, Six Sigma or TOC lies with over focussing on particular method, so those methods are usually used solitary. Complex (i.e. process) approach is usually underestimated. This cannot be changed without changing the way of thinking within all levels of company’s management. Process thinking (lean and holistic) becomes nowadays a challenge. This article is focussing on the use of basic principles of process thinking connected with design, technology and manufacturing logistics with emphasizing the role of standardization. There are debated, based on designed preliminary survey, possible key influences of management stuff etc. to implement and aid principles of standardization as defined by DFx (Design for X).